Fear of Missing Out’s (FoMO) relationship with moral judgment and behavior - McKee, Paul C.; Senthilnathan, Ithika; Budnick, Christopher J.; Bind, Marie-Abèle; Antonios, Imad; Sinnott-Armstrong, Walter (PLOS ONE, 2024)
Across three online studies, we examined the relationship between the Fear of Missing Out (FoMO) and moral cognition and behavior. Study 1 (N = 283) examined whether FoMO influenced moral awareness, judgments, and recalled and predicted behavior of first-person moral violations in either higher or lower social settings. Study 2 (N = 821) examined these relationships in third-person judgments with varying agent identities in relation to the participant (agent = stranger, friend, or someone disliked). Study 3 (N = 604) examined the influence of recalling activities either engaged in or missed out on these relationships. Using the Rubin Causal Model, we created hypothetical randomized experiments from our real-world randomized experimental data with treatment conditions for lower or higher FoMO (median split), matched for relevant covariates, and compared differences in FoMO groups on moral awareness, judgments, and several other behavioral outcomes. Using a randomization-based approach, we examined these relationships with Fisher Tests and computed 95% Fisherian intervals for constant treatment effects consistent with the matched data and the hypothetical FoMO intervention. All three studies provide evidence that FoMO is robustly related to giving less severe judgments of moral violations. Moreover, those with higher FoMO were found to report a greater likelihood of committing moral violations in the past, knowing people who have committed moral violations in the past, being more likely to commit them in the future, and knowing people who are likely to commit moral violations in the future.
Keywords: Behavior; Interpersonal relationships; Machine learning; Memory recall; Moral philosophy; Personality; Religion; Social media; dept.csc; dept.psy; peer-reviewed

Using the Listening2Faces App with Three Young Adults with Autism: A Feasibility Study - Baron, Alisa; Harwood, Vanessa; Woodard, Cooper; Anderson, Kaitlyn; Fernandes, Barbara; Sullivan, Jessica; Irwin, Julia (Advances in Neurodevelopmental Disorders, 2024)
Abstract Objectives Listening2Faces (L2F) is a therapeutic, application-based training program designed to improve audiovisual speech perception for persons with communication disorders. The purpose of this research was to investigate the feasibility of using the L2F application with young adults with autism and complex communication needs. Methods Three young adults with autism and complex communication needs completed baseline assessments and participated in training sessions within the L2F application. Behavioral supports, including the use of cognitive picture rehearsal, were used to support engagement with the L2F application. Descriptive statistics were used to provide (1) an overview of the level of participation in L2F application with the use of behavioral supports and (2) general performance on L2F application for each participant. Results All three participants completed the initial auditory noise assessment (ANA) as well as 8 or more levels of the L2F application with varying accuracy levels. One participant completed the entire L2F program successfully. Several behavioral supports were used to facilitate participation; however, each individual demonstrated varied levels of engagement with the application. Conclusions The L2F application may be a viable intervention tool to support audiovisual speech perception in persons with complex communication needs within a school-based setting. A review of behavioral supports and possible beneficial modifications to the L2F application for persons with complex communication needs are discussed.
Keywords: dept.psy; peer-reviewed

Sleep Health among Children Adopted from Foster Care: The Moderating Effect of Parent–Child Sleep Interactions - Cifre, Anthony B.; Budnick, Christopher J.; Bick, Johanna; McGlinchey, Eleanor L.; Ripple, Carol H.; Wolfson, Amy R.; Alfano, Candice A. (Behavioral Sleep Medicine, 2024)
Keywords: dept.psy; peer-reviewed

A review of the kappa opioid receptor system in opioid use - Cayir, Salih; Zhornitsky, Simon; Barzegary, Alireza; Sotomayor-Carreño, Esteban; Sarfo-Ansah, Wonder; Funaro, Melissa C.; Matuskey, David; Angarita, Gustavo (Neuroscience & Biobehavioral Reviews, 2024)
The kappa opioid receptor (KOR) system is implicated in dysphoria and as an “anti-reward system” during withdrawal from opioids. However, no clear consensus has been made in the field, as mixed findings have been reported regarding the relationship between the KOR system and opioid use. This review summarizes the studies to date on the KOR system and opioids. A systematic scoping review was reported following PRISMA guidelines and conducted based on the published protocol. Comprehensive searches of several databases were done in the following databases: MEDLINE, Embase, PsycINFO, Web of Science, Scopus, and Cochrane. We included preclinical and clinical studies that tested the administration of KOR agonists/antagonists or dynorphin and/or measured dynorphin levels or KOR expression during opioid intoxication or withdrawal from opioids. One hundred studies were included in the final analysis. Preclinical administration of KOR agonists decreased drug-seeking/taking behaviors and opioid withdrawal symptoms. KOR antagonists showed mixed findings, depending on the agent and/or type of withdrawal symptom. Administration of dynorphins attenuated opioid withdrawal symptoms both in preclinical and clinical studies. In the limited number of available studies, dynorphin levels were found to increase in cerebrospinal fluid (CSF) and peripheral blood lymphocytes (PBL) of opioid use disorder subjects (OUD). In animals, dynorphin levels and/or KOR expression showed mixed findings during opioid use. The KOR/dynorphin system appears to have a multifaceted and complex nature rather than simply functioning as an anti-reward system. Future research in well-controlled study settings is necessary to better understand the clinical role of the KOR system in opioid use.
Keywords: Dynorphins; Opioid use disorder; Opioids; dept.psy; peer-reviewed; κ-opioid receptor

Age differences in emotional reactions to ageist memes and changes in age of one's Best Self - Kahlbaugh, Patricia; Ramos-Arvelo, Jacklyn; Brenning, Madison; Huffman, Loreen (Journal of Aging Studies, 2024)
Memes on social media can carry ageist messages and can elicit reactions that are both emotional and self-evaluative. The present study investigates age-related differences in nine discrete emotions and in the evaluation of when individuals have been or will be their best selves. Participants (n = 360) representing young (m = 26 years), middle-aged (m = 39 years) and older adults (m = 63 years) were randomly assigned to view either non-ageist (animals) or ageist (e.g., incompetent older people) memes. After viewing memes, we assessed nine emotional reactions (i.e., fear, anger, sadness, happiness, anxiety, discomfort, disgust, surprise, enjoyment) and Best Self evaluations. Younger and middle-aged people reported more intense emotional reactions to memes than older people, with the exception that older people reported more discomfort and disgust in response to ageist versus non-ageist memes. Younger adults were less surprised by ageist memes (vs. non-ageist) and for all age groups ageist memes (vs. non-ageist) elicited less happiness and enjoyment and were less likely to be shared. With respect to evaluations of one's Best Self, older individuals were more likely to report being their best selves in the past, while after viewing ageist memes, younger individuals were more likely to report being their best selves in the future. Emotions of disgust and discomfort were related to identifying one's Best Self as further in the past. The current study adds to the literature on the impact of ageism by examining age-related differences in the emotions and self-evaluations experienced when confronted with memes on social media.
Keywords: Ageism; Emotions; Self-evaluations; Social media/memes; dept.psy; peer-reviewed

Assessing the efficacy of baselining in deception detection: A comparative analysis of the reality interview and structured interview - Bogaard, Glynis; van de Bovekamp, Anne Margreet; Colwell, Kevin (Acta Psychologica, 2024)
Detecting deception is challenging; there exists no universal cue that gives away deceit and people vary greatly in how they communicate. One way to potentially improve deception detection is by comparing multiple responses of the same individual to identify verbal deviations – a method known as baselining. This study examined the impact of baselining embedded in a specific interview protocol to improve lie detection. Participants (N = 179) viewed mock crimes and were instructed to lie or tell the truth about what they witnessed. Next, they were interviewed including a truthful baseline (Reality Interview Modified: RIM), or no baseline (Reality Interview: RI; Structured Interview: SI). Results showed that truth tellers in the SI and RI conditions provided more details than liars during free recall, while no detail differences emerged for the RIM condition. Follow-up questions in all conditions showed truth tellers offered more details than liars. Surprisingly, we found no evidence that verbal deviations from a baseline can be used as effective indicators of deception. In sum, further research is needed to explore the best application of baselining for lie detection purposes.
Keywords: Baselining; Deception detection; Reality interview; Verbal cues; dept.psy; peer-reviewed

The role of combat exposure on drinking behavior and subjective well-being: A Rubin Causal Model approach. - McKee, Paul; Budnick, Christopher J.; Walters, Kenneth S.; Bind, Marie-Abèle (Psychological Trauma: Theory, Research, Practice, and Policy, 2024)
Keywords: dept.psy; peer-reviewed